Electro-mechanics of resonating nanotubes and nanowires in the field emission environment. (22nd February 2010) - Perisanu, S.; Ayari, A.; Purcell, S.T.; Vincent, P.
In this paper, we review our recent experimental investigations of phenomena associated with the mechanical resonances of nanotubes and nanowires (NN) during field emission (FE). The goal is to show how this configuration can be used for measuring the physical parameters of an NN and how it opens interesting perspectives in the emerging field of Nano Electro-Mechanical Systems (NEMS). In the basic experiment the resonances are excited capacitively in ultra high vacuum (UHV) and are detected by either a variation in the FE current or an increase in the size of the FE pattern. The high electric field also induces a giant tuning of the NN resonance frequency making our NNs tunable oscillators. An image analysis technique has been developed to exploit the FE pattern changes for measuring low vibration amplitudes. High Q-factors of SiC nanowires have been determined as a function of in UHV heating cycles. The effect of the tuning on the resonance frequency has been modelled allowing the extraction of the natural frequency and thus the Young's modulus. Finally, an example of a new NEMS phenomena in the FE configuration is a mechanical 'self oscillations' observed without any AC drive: it is a nanometric DC/AC conversion device.